The Chemical Pneumonitis due to Hydrochloric Acid in Suicide Attempts: Chemical Pneumonitis due to Hydrochloric Acid in Suicide Attempts - Rahadiyanti, Harini; Pratiwi, Suryanti; Astuti, Tri (Malang Respiratory Journal, 2025)
Introduction: Pneumonia cases globally infected 450 million people in 2022, with 25.3% being pneumonitis cases. Chemical pneumonia is inflammation of the lungs caused by chemicals that are acidic or basic. Chemical pneumonia has a mortality of up to 70%. Case report: A 21-year-old female college student came to the emergency room with the chief complaint of shortness of breath and vomiting. The patient has an introvert. From the anamnesis, there was a history of drinking 100 cc of floor cleaning liquid (hydrochloric acid). After 15 minutes she felt nauseous and vomited, accompanied by coughing and shortness of breath due to aspiration. In the CXR, bilateral infiltrates were dominant on the right, and on the CT scan, there was Ground Glass Opacity and fibrosis; the patient was diagnosed with pneumonitis. Clinical improvement was obtained after administering antibiotics and steroids as the main therapy. Patients with a history of drinking chemicals have a risk of aspiration, which can cause complications in the lungs, especially because the material is corrosive. The presence of a gagging reflex causes the liquid to enter the airways. Precise diagnosis can be made with appropriate investigations to minimize the risk of more severe respiratory complications. Conclusion: Chemical pneumonitis can occur in cases of suicide attempts, with fast and appropriate management of anti-inflammatory agents for 7-14 days, which can minimize the risk of respiratory defects and mortality.